Washback of English national exams at ninth-grade level in Thailand and Indonesia - Sundayana, Wachyu; Meekaeo, Panusak; Purnawarman, Pupung; Sukyadi, Didi (Indonesian Journal of Applied Linguistics, 2018)
Washback refers to influences of testing on teaching and learning. In Thailand and Indonesia, washback of the Ordinary National Educational Test (O-NET) and Ujian Nasional (UN) inevitably occurs on teaching and learning in classrooms at every level. This present study aims to explore and compare the washback effects of the O-NET and UN on English language learning as perceived by Thai and Indonesian ninth-grade students. It is a multi-case study (Thailand case and Indonesia case) by using triangulation design as the research design. The questionnaires concerning washback effects of national exams on English language learning were distributed to 200 ninth-graders in the two cases. In addition, six students from each case were interviewed. The results reveal that in both cases, the participants focus to learn on contents and skills that were likely to appear in the national exams. The participants learned English harder to perform well in the tests rather than to improve their English ability. Moreover, the students had high anxiety during the test preparations and feared for low O-NET and UN scores. The results of the study contribute to future washback study and improvement of English language teaching and learning at ninth-grade in Thailand and Indonesia.